Prospek Pengembangan Agribisnis Minyak Kayu Putih di Kecamatan Seram Barat, Kabupaten Seram Bagian Barat - SOUHUWAT, RONALDO; AMBARAWATI, IGAA.; ARGA, IW. (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2014)
The eucalyptus plant (Melaleuca leucadendron Linn) grows well without cultivation in the district of Western Seram, Western Seram Regency. Besides having utility as medicines, eucalyptus oil has high selling value, and as an export commodity. In fact, the potential of this commodity in this region has not been managed and developed optimally.  The aims of this research are to analyze profitability and the internal and external factors of eucalyptus oil agribusiness development in the District of Western Seram, and to formulate the strategy that must be done by producers of eucalyptus oil and alternative strategies for its agribusiness development. The results showed that eucalyptus oil agribusiness in the District of Western Seram                   is profitable, shown by the value of R/C is equal to 1.90. The influential factors according to the score of internal factors (IFAS) are the wide potential land, the availability of raw materials, and limited capital of the producers. While the prominent external factors (EFAS) are the availability of market, competition from Buru Island, and flammable eucalyptus forest.  The main strategy to be applied is market penetration and product development. Strategic alternatives include: (1) Expansion of market share through government policy on development of small medium enterprises; (2) Improvement of product and its quality through pest and disease control, monitoring time of fire prone, eucalyptus development based on regional sites, and establishment of institutions to deal with the competition; (3) Improvement packaging concepts through the implementation of modern technology; (4) Capital improvement through the supports from government and financial institutions; (5) Improvement of production and product prices through eradication of pests or diseases and the prevention of forest fires; and    (6) Establishment of the farmer groups as mediator between producers and processing interests including marketing institutions.
Keywords: eucalyptus oil, prospect, agribusiness, internal-external factors, strategies